Room-temperature ultraviolet laser emission from ZnO hexagonal microprisms and nanowires - Kapustianyk, V.; Turko, B.; Rudyk, Y.; Tsybulskyi, V.; Rudyk, V.; Vaskiv, A. (Физическая инженерия поверхности, 2015)
We report the observation of optically pumped laser generation in ZnO microprisms and nanowires at room temperature. The ZnO microprisms were grown on the single crystal (100) silicon substrates by a solid-vapor-phase process. The ZnO nanowires were grown on a glass substrate coated with indium tin oxide by the electrochemical deposition. Laser effect was observed at room temperature at the optically pump power higher than 685 kW cm⁻² for ZnO microprisms and 560 kW cm⁻² — for ZnO nanowires.